EVALUATION OF THE WOOD QUALITY OF PLATINUM TEAK WOOD - Adi, Danang Sudarwoko (Teknologi Indonesia, 2016)
The quality of platinum teak wood (Tectona grandis), which is developed by Indonesian Institute of Sciences(LIPI) through tissue culture method was observed in this study. The aims were to asses and evaluate the woodquality, i.e. physical and mechanical properties, and also to investigate the potential use as well as the challengeof this wood in the future compared to others wood, especially with the conventional ones. Two-year-old platinumteak wood was analyzed for physical properties, while five-year-old platinum weak was analyzed for physicaland mechanical properties. Both of these woods were planted in Cibinong, Bogor. Ten-year-old teak wood fromcommunity forest in Serpong, Tangerang and secondary data from various conventional teak woods from variousregions were used as comparisons. The results show that physical properties of 2-and 5-year-old platinum teakwood are better than 10 years teak wood from community forest. The basic densities of 2-and 5-year-old platinumteak wood are 0.50 and 0.53 g/cm3, respectively, while ten-year-old community forest teak wood is 0.42 g/cm3. Thedimensional stability of 5 years platinum teak wood is low and similar to ten-year-old community and progeny testteak wood, which the value of tangential and radial ratio (TR ratio) of this wood is 2.16. TR ratio of two-year-oldplatinum teak wood is ~1. The MOR of five-year-old platinum teak wood is 919.79 kg/cm2. This value is almostsimilar to 2030-year-old conventional teak wood from East Java. Almost all of wood qualities depend on age ofthe trees. Therefore, it is predicted that platinum teak wood has a good potency to be used for structural applicationsas well as for furniture.